Socio-Economic Background of the Employees in MSN Laboratories Hyderabad - Rani, Prof. Dara Sheaba; Ranjitha, Guntupalli Sri; Venkatarattaiah, Kundeti (IJRDO - Journal of Business Management, 2017)
At the outset an attempt is made in this paper to discuss the socio-economic background of 380 respondents in Manne Satyanarayana Reddy Laboratories. The study reveals that a vast majority of 86.6 per cent of the respondents are belonging to the age group of 20-39 years. A whopping majority of 79.2 per cent of them are Hindus. The education list is topped by the M.Pharmacy and P.G holders with 72.4 per cent. About 47.9 per cent of the respondents are migrants. The respondents’ adequate opinion on family financial position is 47.6 per cent. It is to be noted that the respondents are spending more money on food consumption followed by shelter and clothing. About 51.3 per cent of them are residing in rented houses and 42 per cent of the sample respondents are having own houses. The study found that about 55 per cent of the respondents took loan from different sources to meet their day to day necessities.